Physics and Metaphysics in Descartes and in his Reception
1 online resource (300 pages)
Keywords: This volume explores the relationship between physics and metaphysics in Descartes’ philosophy. According to the standard account, Descartes modified the objects of metaphysics and physics and inverted the order in which these two disciplines were traditionally studied. This book challenges the standard account in which Descartes prioritizes metaphysics over physics. It does so by taking into consideration the historical reception of Descartes and the ways in which Descartes himself reacted to these receptions in his own lifetime. The book stresses the diversity of these receptions by taking into account not only Cartesianisms but also anti-Cartesianisms, and by showing how they retroactively highlighted different aspects of Descartes’ works and theoretical choices. The historical aspect of the volume is unique in that it not only analyzes different constructions of Descartes that emerged in the 18th, 19th and 20th centuries, but also reflects on how his work was first read by philosophers across Europe. Taken together, the essays in this volume offer a fresh and up-to-date contribution to this important debate in early modern philosophy.